Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Layanan Pendidikan Anak Usia Dini di Era Kurikulum Merdeka - Nurhasanah R; Nursidah Nursidah; Fahri Abdullah; Ristina Ristina (Institusi Agama Islam Negeri (IAIN) Bone, 2025)
This study aims to describe the leadership strategy of PAUD heads in improving the quality of early childhood education services during the implementation of the Independent Curriculum. The focus of this research is Pattola Palallo Kindergarten, Awangpone District, Bone Regency. The method used is qualitative research with a case study approach. Data was collected through observation, in-depth interviews, and documentation, then analyzed in a qualitative descriptive manner. The results of the study showed that kindergarten heads implemented participatory and transformative leadership strategies through needs-based program planning, continuous teacher coaching, and strengthening cooperation with parents and the community. This strategy has an impact on improving teacher professionalism, creating a child-friendly learning environment, and increasing parental involvement in the education process. Despite being faced with limited resources, kindergarten heads are able to manage challenges with a collaborative and innovative approach. This study concludes that the adaptive and responsive leadership of PAUD heads to the Independent Curriculum policy plays an important role in realizing quality early childhood education services. This finding is expected to be a reference for other PAUD heads in developing leadership strategies that are in accordance with the demands of the times.